Exploring the Underlying Mechanism of Weiling Decoction Alleviates Cold-Dampness Diarrhea Based on Network Pharmacology, Transcriptomics, Molecular Docking and Experimental Validation - Yannan Zhang; Shuai Zhang; Yimeng Fan; Sijuan Huang; Shimin Wang; Zhihui Hao; Jianzhong Shen (Pharmaceuticals)
Background: Cold-dampness diarrhea (CDD) is a common gastrointestinal disorder in children, characterized by diarrhea and intestinal barrier dysfunction. Weiling decoction (WLD) is frequently used in clinical practice to treat CDD, a condition triggered by multiple factors. However, the molecular mechanisms underlying its therapeutic effects remain poorly understood. Objectives: This study aimed to evaluate the efficacy of WLD in treating CDD and to elucidate its potential mechanisms. Methods: UPLC-HRMS/MS was employed to identify the chemical constituents of WLD and the absorption components in the plasma of WLD-treated rats. Additionally, a rat model of CDD was established to assess the therapeutic effects of WLD through a comprehensive approach. To elucidate the molecular mechanisms underlying these effects, network pharmacology and transcriptomic analyses were performed to identify potential signaling pathways associated with CDD alleviation. Molecular docking and flow cytometry assays were subsequently utilized to validate the identified signaling pathways. Results: A total of 223 chemical components were detected in WLD, and 49 absorption components were identified in the plasma of WLD-treated rats by UPLC-HRMS/MS. WLD treatment significantly alleviated the symptoms of CDD, reduced intestinal damage, and diminished the inflammatory response. Additionally, WLD influenced key genes in immune-related pathways. Molecular docking revealed strong binding affinities between the main components of WLD and key targets within these pathways. Flow cytometry, along with the analysis of inflammatory cytokines and transcription factors, demonstrated that WLD modulated the balance between Th1/Th2 and Th17/Treg cell populations. Conclusions: This study provides the first evidence that WLD alleviates CDD by regulating the balance between Th1/Th2 and Th17/Treg cell populations. These findings offer a theoretical basis for future investigations into the therapeutic potential of WLD in the treatment of CDD.